L’età dell’oro sotto Vr̥tra e la formula indoeuropea ‘terra inarata’ (Atti del Sodalizio Glottologico Milanese, 2017)
In a Rāmāyaṇa passage Vr̥tra is represented as a king of the Golden Age. Virtuous, pious and compassionate, he is killed by a ruthless Indra. The meaning of such an anomalous episode is analyzed in the light of the dumezilian comparative method. KEYWORDS: Sanskrit, Indo-European, Golden Age, cultural reconstruction, Indo-European myth